2022
DOI: 10.1177/23259671221127721
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth Physical Therapy for Sports Medicine Rehabilitation: What Is Its Role in the Postpandemic Era?

Abstract: Background: The adoption of telehealth visits for physical therapy (PT) has accelerated because of the COVID-19 pandemic. Patient reception of virtual PT at the outbreak of the pandemic was positive, but it is unclear how telehealth visits compare to in-person visits in the postpandemic era. Purpose: To evaluate utilization trends and patient satisfaction with virtual PT compared with in-person PT during and after the COVID-19 pandemic. Study Design: Cross-sectional study; Level of evidence, 3. Methods: We ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In contrast to the existing research literature, in which authors report mixed effects, patient experience did not differ between hybrid and in-clinic-only cases in this study. In a previous study of 205 patients who received telerehabilitation or home rehabilitation following a total knee replacement, Moffet and colleagues (2016) reported that patient satisfaction was high for both groups and not significantly different [43]. Yet, in a cross-sectional study including over 1000 patients with sports medicine needs treated during COVID-19 and the immediate post-pandemic period, Kim and colleagues (2022) observed significant differences in patient experience scores in the proportion of promoters on the NPS (telehealth: 75% vs. in-clinic: 89% promoters, p = 0.008), suggesting that patient experience was poorer for telehealth patients [44].…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to the existing research literature, in which authors report mixed effects, patient experience did not differ between hybrid and in-clinic-only cases in this study. In a previous study of 205 patients who received telerehabilitation or home rehabilitation following a total knee replacement, Moffet and colleagues (2016) reported that patient satisfaction was high for both groups and not significantly different [43]. Yet, in a cross-sectional study including over 1000 patients with sports medicine needs treated during COVID-19 and the immediate post-pandemic period, Kim and colleagues (2022) observed significant differences in patient experience scores in the proportion of promoters on the NPS (telehealth: 75% vs. in-clinic: 89% promoters, p = 0.008), suggesting that patient experience was poorer for telehealth patients [44].…”
Section: Discussionmentioning
confidence: 97%
“…Following the dramatic increase in use of telehealth healthcare during 2020, there has been published research into a range of aspects of telehealth (attitudes, confidence, use, acceptability, satisfaction) across many health professions, including registered physiotherapists (Albahrouh & Buabbas, 2021; Barton et al., 2022; Davies et al., 2022; Kim et al., 2022; Merolli et al., 2022; Pegorari et al., 2020). However, there has been less focus on telehealth delivery by allied health students, particularly physiotherapy students.…”
Section: Introductionmentioning
confidence: 99%